Rapid germination and development of Acacia sieberiana DC in vitro - Hussein M. DAFFALLA; Kauther S. ALI; Magdoleen G. OSMAN; Yousif O. YAHIYA (Notulae Scientia Biologicae, 2022)
Acacia sieberiana is an ecological and economical important forest tree. The plant has poor germination due to dormancy; therefore, in vitro culture can provide a fast supply of plantlets and can be a basis for further biotechnology research. The effect of sodium hypochlorite, Murashige and Skoog (MS) medium, sucrose and cytokinin were investigated. The results indicated that all the treatments induced significant (P < 0.05) effects on germination and seedling development depending on their concentrations. Germinates free of contamination were established successfully with all the concentrations of sodium hypochlorite, however, the germination was reduced as the concentration increased. A higher germination rate of 98.3% was attained with full MS strength and 3% sucrose concentration. The highest germination percentage obtained was 100% with 2 mg/L thidiazuron. The maximum shoot length (13.5 cm) and seedling dry weight (0.49 g) were recorded on full MS medium while the maximum root length (13.4 cm) was obtained on ½ MS strength. However, when full MS medium augmented with 5% sucrose enhanced shoot length and dry weight to (14.2 cm) and (0.5 g), respectively. While the highest root length (10.2 cm) was obtained by 3% provided in full MS medium. Application of cytokinins improved the number of node and dry weight of seedlings to 6.9 nodes with 4 mg/L thidiazuron and 0.54 g by 2 mg/L benzyladenine. The present study describes the establishment of in vitro seed germination and seedling growth system for A. sieberiana for the first time.